N-terminal pro-B-type natriuretic peptide measurement is useful in predicting left ventricular hypertrophy regression after aortic valve replacement in patients with severe aortic stenosis - Lee, Mirae (Heart Asia, 2015)
BACKGROUND: The predictive factors for early left ventricular hypertrophy (LVH) regression after aortic valve replacement (AVR) have not been fully elucidated. This study was conducted to investigate which preoperative parameters predict early LVH regression after AVR. METHODS AND RESULTS: 87 consecutive patients who underwent AVR due to isolated severe aortic stenosis (AS) were analysed. Patients with ejection fraction <50% or concomitant coronary artery disease were excluded from the analysis. Preoperative evaluation including echocardiography and N-terminal pro-B-type natriuretic peptide (NT-proBNP) measurement was performed and midterm follow-up echocardiography was done at a median of 9 months after AVR. The presence of complete regression of LVH at the midterm follow-up was determined. In multivariate analysis, including preoperative echocardiographic parameters, only E/e′ ratio was associated with midterm LVH regression (OR 1.11, 95% CI 1.01 to 1.22; p=0.035). When preoperative NT-proBNP was added to the analysis, logNT-proBNP was found to be the single significant predictor of midterm LVH regression (OR 2.00, 95% CI 1.08 to 3.71; p=0.028). By receiver operating characteristic curve analysis, a cut-off value of 440 pg/mL for NT-proBNP yielded a sensitivity of 72% and a specificity of 77% for the prediction of LVH regression after AVR. CONCLUSIONS: Preoperative NT-proBNP was an independent predictor for early LVH regression after AVR in patients with isolated severe AS.